Unveiling crustal intrusions and fault systems of southwestern Sokoto Basin through enhanced gravity analysis - ABUBAKAR, Adamu; LIKKASON, Othniel Kamfani; YUNUSA, Abdulganiyu (Contributions to Geophysics and Geodesy, 2025)
The Sokoto Basin, a frontier basin area in northwestern Nigeria, has garnered significant attention due to its favourable prospects for oil and gas exploration. This study utilises potential field gravity data to investigate the depth architecture of the southwestern Sokoto Basin and provide insights into the emplacement mechanisms of its anomalous geological features. The Bouguer gravity anomaly reveals a regional gravity field dipping at approximately 10° northeasterly, with a gradient of 0.38 mGal/km. Residual Bouguer anomaly analysis identifies a prominent positive anomaly in the southern region and negative anomalies ranging from −74.88 mGal to −27.38 mGal. Integration of enhancement filters, forward modelling, and spectral analysis reveals that source depths increase towards the south. Gravity modelling indicates intrusions in the upper crust at depths of 10 to 20 km and 5 to 10 km. A 3D model assembled from the findings illustrates the basin’s subsurface structure, supporting earlier works. The results suggest that Eocene sediments and Quaternary faults/fractures play critical roles in the area’s hydrocarbon system. Ultimately, the quantitative analysis of the gravity maps reveals the presence of diverse structural features and their constituent components within the study area. Notably, the primary tectonic deformations exhibit trends oriented NW–SE, NE–SW, and E–W. This study significantly enhances our understanding of the subsurface architecture of the southwestern Sokoto Basin, offering crucial insights that will inform and optimise future hydrocarbon exploration initiatives.